2013
DOI: 10.1111/cns.12175
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Potential of Silymarin against CNS Disorders: Insight into the Pathways and Molecular Mechanisms of Action

Abstract: Silymarin, a C25 containing flavonoid from the plant Silybum marianum, has been the gold standard drug to treat liver disorders associated with alcohol consumption, acute and chronic viral hepatitis, and toxin-induced hepatic failures since its discovery in 1960. Apart from the hepatoprotective nature, which is mainly due to its antioxidant and tissue regenerative properties, Silymarin has recently been reported to be a putative neuroprotective agent against many neurologic diseases including Alzheimer's and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(54 citation statements)
references
References 79 publications
(126 reference statements)
1
49
0
1
Order By: Relevance
“…As indicated earlier, previous studies have shown that SM treatment can increase serotonin levels in the PFC in mice (Lu et al, 2010;Borah et al, 2013). We and others have shown that the PFC and the serotoninergic system in the brain play important roles in regulating anxietyrelated behaviors in humans and rodents (Davidson, 2002;Akimova et al, 2009;Solati et al, 2011).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…As indicated earlier, previous studies have shown that SM treatment can increase serotonin levels in the PFC in mice (Lu et al, 2010;Borah et al, 2013). We and others have shown that the PFC and the serotoninergic system in the brain play important roles in regulating anxietyrelated behaviors in humans and rodents (Davidson, 2002;Akimova et al, 2009;Solati et al, 2011).…”
Section: Discussionmentioning
confidence: 52%
“…There is increasing evidence from clinical and experimental studies that silymarin (SM), a mixture of flavonolignans including silybin, silydianin, and silychristin extracted from the milk thistle (Silybum marianum), can be used as a hepatoprotective, antioxidative, antiinflammatory, or neuroprotective drug (for a review, see Borah et al, 2013). Previous studies have also indicated that SM can influence cytokine production, RNA and protein synthesis, scavenging of free radicals, and stabilization of the cell membrane (Gupta et al, 2000;Li et al, 2006;Wu et al, 2009;Patel et al, 2010;Muley et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Several authors propose antioxidants as good neuroprotective agents for brain ischemia, even though some of them, edaravone, sylimarin, minocycline or quercetin, among others, have not shown efficacy in clinic (7,(42)(43)(44)(45)(46). In line with this, because melatonin is a direct and indirect antioxidant, it has been proposed as a neuroprotective agent (47) and it has shown to be a good candidate, as it has demonstrated neuroprotection against oxidative stress implied in different neurodegenerative diseases such as AD (48,49), PD (50,51), brain trauma (52) and…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Many natural and/or endogenous compounds have recently been shown to be effective in rodent models of PD as well, such as resveratrol [2628], tanshinone [29,30], silymarin [3135], resolvins [36], diadzein [37], and apocynin derivatives [38,39]. The majority of these compounds act as both anti-inflammatory agents as well as anti-oxidants.…”
Section: Introductionmentioning
confidence: 99%